Metabolic syndrome is not associated with erectile dysfunction in apparently healthy men - Susanna Kuneinen; Risto J. Kaaja; Tero J. Vahlberg; Päivi E. Korhonen (ELSEVIER SCI LTD, 2022)
Aims: To investigate whether metabolic syndrome (MetS) is associated with erectile dysfunction (ED) among apparently healthy men when depressive symptoms and serum testosterone levels are taken into account.
Methods: A study population of 549 men at risk for cardiovascular disease or type 2 diabetes was drawn from the participants of a population survey, the Harmonica Project. MetS was diagnosed with the United States National Cholesterol Education Program Third Adult Treatment Panel (ATPIII) 2005 definition, the International Diabetes Federation (IDF) 2005 definition and the Harmonization 2009 definition. ED was evaluated by the International Index of Erectile Function (IIEF-5) questionnaire. Depressive symptoms were assessed with Beck's Depression Inventory (BDI).
Results: Of the 549 men (mean age 58.4 +/- 6.7 years), 56.5 % reported ED. The prevalence of MetS was 48.6%, 35.5%, and 50.6% according to the IDF, the ATPIII, and the Harmonization criteria, respectively. We found no difference in the prevalence of ED between men with or without MetS. In a multivariate analysis, age, presence of depressive symptoms and lower education were significant predictors of ED.
Conclusions: The prevalence of ED is quite high even in apparently healthy men. Depressive symptoms are a critical component to consider in men suffering from ED.